(untitled) (Journal of Student Affairs in Africa, 2021)
Amongst the first of the challenges facing prospective first-year university students is the need to procure funding for their studies. Indeed, demand for funding for students to access higher education far exceeds supply in South Africa. One solution has been the creation of a government loan scheme, the National Student Financial Aid Scheme (NSFAS), but this scheme does not cover all students. Outside of NSFAS, student bursary funding remains limited and universities are being increasingly pressurised to allocate bursaries to ensure students are not excluded due to funding constraints. Despite this, to date, little work has been undertaken regarding university policy and management of bursary applications and funds. Thus this study represents an attempt to fill this gap. The study explores the current student funding model deployed at one particular large tertiary institution as a means to gain an understanding of current funding challenges and attempt to find ways in which funding decisions can be improved. A qualitative approach was used, which involved conducting in-depth interviews with senior university staff involved in a range of student support directorates. The study demonstrates the complexity of the challenges associated with student funding.